The Contextual Effect of School on Smoking Behavior among Male High School Students - Tria Arifianti; RB. Soemanto; Hanung Prasetya (Journal of Health Promotion and Behavior, 2019)
Background: Indonesia was a country with high cigarette production and consumption. The smoking prevalence in adolescents aged 13-15 years in several countries included Argentina (3.7%), Egypt (3.7%), America (3.4%) and Indonesia (2.8%). The impact of cigarette exposure both as active and passive smokers such as the occurrence of various diseases included impotence, various types of cancer, respiratory diseases, coronary heart disease and others. This study aimed to analyze the contextual effect of school on smoking behavior among students.Subjects and method: This was a cross sectional study conducted in Bantul, Yogyakarta, from April to May 2019. A sample of 200 male adolescents was selected by stratified random sampling. The dependent variable was smoking behavior. The independent variables were knowledge, family role, peer role, cigarette price, pocket money, and attitude. The data were collected by questionnaire. The data were analyzed by a multilevel multiple logistic regression run on Stata 13.Results: Smoking behavior was negatively associated with poor knowledge (b= -3.30; 95% CI= -0.35 to -0.09; p= 0.001), strong family role (b= -3.11; 95% CI= -1.15 to -0.26; p= 0.002), strong peer role (b= -3.92; 95% CI= -1.10 to -0.36; p< 0.001), cigarette price <Rp 10,000 (b= -2.81; 95% CI= -1.10 to -0.19; p= 0.005), money pocket >Rp 300,000 (b= -3.79; 95% CI= -5.75 to -0.01; p<0.001), and negative attitude (b= -3.37; 95% CI= -0.15 to -0.05; p = 0.001). School had contextual effect on smoking behavior with ICC= 14.00%.Conclusion: Smoking behavior is negatively associated with poor knowledge, strong family role, strong peer role, low cigarette price, high money pocket, and negative attitude. School has contextual effect on smoking behavior.Keywords: smoking behavior, adolescents, peers, multilevel analysisCorrespondence: Tria Arifianti. Masters Program in Public Health. Universitas Sebelas Maret. Jl. Ir. Sutami 36A,  Surakarta 57126, Central Java. Email: tria.arifianti@gmail.com. Mobile: +6285866515112.Journal of Health Promotion and Behavior (2019), 4(1): 76-84https://doi.org/10.26911/thejhpb.2019.04.01.08